Novel Targeting to XCR1+ Dendritic Cells Using Allogeneic T Cells for Polytopical Antibody Responses in the Lymph Nodes - Kitazawa, Yusuke; Ueta, Hisashi; Sawanobori, Yasushi; Katakai, Tomoya; Yoneyama, Hiroyuki; Ueha, Satoshi; Matsushima, Kouji; Tokuda, Nobuko; Matsuno, Kenjiro (Frontiers in Immunology, 2019)
Vaccination strategy that induce efficient antibody responses polytopically in most lymph nodes (LNs) against infections has not been established yet. Because donor-specific blood transfusion induces anti-donor class I MHC antibody production in splenectomized rats, we examined the mechanism and significance of this response. Among the donor blood components, T cells were the most efficient immunogens, inducing recipient T cell and B cell proliferative responses not only in the spleen, but also in the peripheral and gut LNs. Donor T cells soon migrated to the splenic T cell area and the LNs, with a temporary significant increase in recipient NK cells. XCR1+ resident dendritic cells (DCs), but not XCR1– DCs, selectively phagocytosed donor class I MHC+ fragments after 1 day. After 1.5 days, both DC subsets formed clusters with recipient CD4+ T cells, which proliferated within these clusters. Inhibition of donor T cell migration or depletion of NK cells by pretreatment with pertussis toxin or anti-asialoGM1 antibody, respectively, significantly suppressed DC phagocytosis and subsequent immune responses. Three allogeneic strains with different NK activities had the same response but with different intensity. Donor T cell proliferation was not required, indicating that the graft versus host reaction is dispensable. Intravenous transfer of antigen-labeled and mitotic inhibitor-treated allogeneic, but not syngeneic, T cells induced a polytopical antibody response to labeled antigens in the LNs of splenectomized rats. These results demonstrate a novel mechanism of alloresponses polytopically in the secondary lymphoid organs induced by allogeneic T cells. Donor T cells behave as self-migratory antigen ferries to be delivered to resident XCR1+ DCs with negligible commitment of migratory DCs. Allogeneic T cells may be clinically applicable as vaccine vectors for polytopical prophylactic antibody production even in asplenic or hyposplenic individuals.